Draft genome sequence and SSR data mining of “pumpo” (Bos taurus), a top bull from a peruvian genetic nucleus - Estrada Cañari, Richard; Romero Avila, Yolanda; Figueroa Venegas, Deyanira Antonella; Quilcate Pairazaman, Carlos Enrique; Casanova Nuñez Melgar, David Pavel; Vásquez Pérez, Hector Vladimir; Alvarado Chuqui, Wigoberto; Maicelo Quintana, Jorge Luis; Arbizu Berrocal, Carlos Irvin (MDPI, 2024)
Pumpo is a Simmental breed and an essential livestock resource in the nucleus genetic cattle of Peru. This study provides a draft genome sequence of a top bull using a de novo assembly approach on the Illumina Novaseq X platform, yielding 208 GB of raw sequencing data with 150 bp paired‐end reads. The final genome assembly resulted in a size of 2.06 Gb with an N50 contig length of 108 Mb and a completeness of 95.7% according to BUSCO analysis. A total of 973,925 simple sequence repeats (SSRs) were identified, with a predominance of mononucleotide repeats. The genome showed low heterozygosity (0.568%) and moderate repeatability (11.5%), aligning with other Bos taurus genomes. Reference‐guided scaffolding improved the assembly quality significantly, producing an N50 scaffold value of 108 Mb. The SSR analysis of the Pumpo genome identified 973,925 SSRs with a frequency of 2,808 SSRs per kilobase, predominantly mononucleotide repeats, and 85,453 found in compound formations. Obtaining knowledge of the genome of a breeding Simmental bull is essential to optimize breeding programs and improve productivity.